The Invisible Learning Ceiling: Informal Learning Among Preschool Teachers and Assistants in a Norwegian Kindergarten. (18th June 2015) - Schei, Vidar; Nerbø, Ida
Abstract : Individuals and society invest ever‐increasing resources in formal educational programs. However, informal workplace learning may be an effective alternative source for enhancing competencies, but, unfortunately, our knowledge about informal learning is still limited. We extend the research on informal learning to the unexplored occupational group of kindergarten employees. Our research questions pertain to identifying activities that lead to informal learning, to conditions that promote or prevent such learning, and to differences between two groups of employees (preschool teachers and assistants). We used a qualitative case‐study approach and conducted semistructured, in‐depth interviews in a Norwegian kindergarten. The data indicated that the participants were involved in a variety of learning activities. However, preschool teachers and assistants differed regarding the conditions for informal learning, with assistants perceiving greater barriers to learning in the workplace. We argue that the assistants are easily trapped in situations in which further learning is difficult, and, paradoxically, those employees with the lowest formal education also seem to be disfavored with regard to informal learning. Clever organization of the work and careful leadership might be key actions to break through this invisible learning ceiling.